Physical and Numerical Modeling of the Manufacturing Process of a Complex Shape Pressed Element from a Nickel Superalloy - M. Hyrcza-Michalska (Archives of Metallurgy and Materials, 2020)
Products of complex geometry, aerodynamic shape and high quality surface finishes are among the most difficult to produce by using stamping methods. When additionally materials with special properties are intended, the task of determining their technological character becomes difficult to solve without the use of physical and numerical methods of process modeling. The paper presents the results of modeling the process of producing a single tube of the jet engine tubular diffuser subassembly. This is a product representative of such a complex geometry one. The charge material for this element requires resistance to operating conditions at elevated temperature and high durability. Therefore, an Inconel type nickel superalloy was proposed for the charge material. In the solution of designing the method of producing a single diffuser tube task, the capabilities of the AutoGrid automatic strain analyzer and the FEM simulation software Eta / Dynaform 5.9 were combined. Numerical simulations of different variants of the manufacturing process of the diffuser tube were made using the Eta / Dynaform 5.9 software. The results of forming simulations became the basis for the alternative technological cycle design of this drawpiece.